SISTEM PENGELOLAAN BARANG BUKTI DAN BARANG RAMPASAN DI KEJAKSAAN NEGERI JAKARTA UTARA PADA LINGKUP KEJAKSAAN REPUBLIK INDONESIA - Tirayudi, Jemmy Novian; Nurati, Dian Esti; Wangi, Maya Sekar (JI@P, 2020)
The objective of research is to study and to analyze the evidence and loot management system in North Jakarta District Attorney in Republic of Indonesia’s Attorney Scope. Organization development at North Jakarta District Attorney level in Republic of Indonesia’s Attorney Scope has not been supported by the presence of stipulation in the form of Standard Operating Procedure in implementing the duty and function of evidence and loot management system, so that the implementation of such duty and function has not run optimally either structurally or hierarchically leading to vulnerability to internal conflict occurring in the organization recalling the evidence and loot management section in North Jakarta District Attorney refers to an internal consensus of organization only in implementing its duty and function. The result of research showed that, viewed from organizational management function, the evidence and loot management system in North Jakarta District Attorney in Republic of Indonesia’s Attorney Scope, involving planning, organization, activation, and coordination, indicates the presence of planning in structural development not supported with operational stipulation in the form of standard operating procedure. Then, its structural organization has not functioned optimally in its hierarchy in the implementation of authority and responsibility, while in the term of activation, it can be seen the leadership that use its discretion in looking for the solution to the implementation of duty and function in evidence and loot management section and the coordination in the structure in North Jakarta District Attorney has not set forth the equality principle in structure, because the role of structure has not been seen clearly, but there is coordination at bottom level, so that the form of responsibility in hierarchy level is still vulnerable to the internal conflict by blaming each other.